Peroxisome Proliferator-Activated Receptors in Female Reproduction and Fertility - Maurizio Vitti; Giovanna Di Emidio; Michela Di Carlo; Gaspare Carta; Andrea Antonosante; Paolo Giovanni Artini; Annamaria Cimini; Carla Tatone; Elisabetta Benedetti (PPAR Research)
Reproductive functions may be altered by the exposure to a multitude of endogenous and exogenous agents, drug or environmental pollutants, which are known to affect gene transcription through the peroxisome proliferator-activated receptors (PPARs) activation. PPARs act as ligand activated transcription factors and regulate metabolic processes such as lipid and glucose metabolism, energy homeostasis, inflammation, and cell proliferation and differentiation. All PPARs isotypes are expressed along the hypothalamic-pituitary-gonadal axis and are strictly involved in reproductive functions. Since female fertility and energy metabolism are tightly interconnected, the research on female infertility points towards the exploration of potential PPARs activating/antagonizing compounds, mainly belonging to the class of thiazolidinediones (TZDs) and fibrates, as useful agents for the maintenance of metabolic homeostasis in women with ovarian dysfunctions. In the present review, we discuss the recent evidence about PPARs expression in the hypothalamic-pituitary-gonadal axis and their involvement in female reproduction. Finally, the therapeutic potential of their manipulation through several drugs is also discussed.